Analisis Komparatif Biaya Angkutan Milik Sendiri dengan Sewa pada Pengiriman Beras Bulog Oleh PT Pos Logistik Indonesia – Branch Bandung - Suryo Mukti Rury, Febrianbaqi; Syafrianita Syafrianita; Nurlaela Kumala, Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
PT Pos Logistik Indonesia (POSLOG) is a company that provides integrated logistics services across various sectors. One of the main commodities delivered regularly each year is rice from Bulog, which has a significant distribution volume. At present, PT Pos Logistik Indonesia – Branch Bandung still relies on third-party (vendor) transportation services, which leads to suboptimal company revenue and creates dependency on external parties. This study aims to conduct a comparative analysis of operational cost efficiency between the use of company-owned vehicles and rented vehicles. The analytical methods applied include Vehicle Operating Costs (VOC), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The analysis results show that the cost of using vendor services amounts to IDR 710 per kilogram, while the cost of using company-owned vehicles is only IDR 284 per kilogram. Furthermore, the NPV value reached IDR 2,732,364,981, the IRR was 129.94%, and the Payback Period was 1 year and 9 months. Based on these findings, investing in company-owned vehicles is proven to be more efficient, economical, and feasible to improve profitability and ensure business sustainability.